2021
DOI: 10.3390/ncrna7030040
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in Epilepsy of Tuberous Sclerosis Complex: Carriers of Pro-Inflammatory MicroRNAs

Abstract: Exosomes are a class of small, secreted extracellular vesicles (EV) that have recently gained considerable attention for their role in normal cellular function, disease processes and potential as biomarkers. Exosomes serve as intercellular messengers and carry molecular cargo that can alter gene expression and the phenotype of recipient cells. Here, we investigated alterations of microRNA cargo in exosomes secreted by epileptogenic tissue in tuberous sclerosis complex (TSC), a multi-system genetic disorder tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…However, it was found to demonstrate a connection with the mTOR pathway; treatment of melanoma cells with the flavonoid Licochalcone A resulted in elevated miR-142-3p expression, followed by the inhibition of the target gene Rheb and the suppression of the mTOR signaling pathway [ 21 ]. Furthermore, miR-142-3p was found to be significantly increased in epileptogenic tubers of TSC patients, initiating a neuroinflammatory cascade [ 22 ]. Another report indicated that miR-142-3p and miR-142-5p were significantly decreased in the mitochondrial fraction and increased in the cytoplasmic fraction at early time points following traumatic brain injury [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found to demonstrate a connection with the mTOR pathway; treatment of melanoma cells with the flavonoid Licochalcone A resulted in elevated miR-142-3p expression, followed by the inhibition of the target gene Rheb and the suppression of the mTOR signaling pathway [ 21 ]. Furthermore, miR-142-3p was found to be significantly increased in epileptogenic tubers of TSC patients, initiating a neuroinflammatory cascade [ 22 ]. Another report indicated that miR-142-3p and miR-142-5p were significantly decreased in the mitochondrial fraction and increased in the cytoplasmic fraction at early time points following traumatic brain injury [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-19a/b-3p/SIRT1 promotes neuroinflammation by regulating FoxO3/SPHK1 signalling, leading to cell death [ 32 ]. miR-146a and 142-3p are involved in the TLR signalling pathway [ 58 , 59 , 60 ]. miR-672 and 135b-5p are related to the pyroptosis pathway [ 36 , 37 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In epileptogenic tissue, the genetic material activated in vitro was highly elevated. These findings provide an additional understanding of the role of exosomes and non-coding RNA cargo in the epileptic neuroinflammatory cascade, potentially leading to the development of new biomarkers and treatments for drug-resistant epilepsy [ 151 ].…”
Section: Therapeutic Applications Of Exosomesmentioning
confidence: 99%